![{a}^{ \frac{logb(lob \: x)}{logb \: a} } {a}^{ \frac{logb(lob \: x)}{logb \: a} }](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B+%5Cfrac%7Blogb%28lob+%5C%3A+x%29%7D%7Blogb+%5C%3A+a%7D+%7D+)
solve this problem it is important
Answers
Answered by
1
Answer:
Given that
=a^log (b)(log_b (x))/log_b(a)
=a^log(b)(log ( x) / log(b)/log(a)/log(b)
=a^log(x)×log (b)/log (a)
=a^log(x) × log_a(b)
=(a^log_a (b)^log(x)
= b^log(x)
Answered by
0
Answer:
Please follow me and like the answer which I have solved past friends please. please mark me as a brainlist
Attachments:
![](https://hi-static.z-dn.net/files/d0c/1160d75b2bff5c8861dea221046c8c2d.jpg)
Similar questions
English,
5 months ago
Math,
10 months ago
Psychology,
10 months ago
English,
1 year ago
Chemistry,
1 year ago